First reported case of per anal endoscopic myectomy (PAEM): A novel endoscopic technique for resection of lesions with severe fibrosis in the rectum - Rahni, David Ozzie; Toyonaga, Takashi; Ohara, Yoshiko; Lombardo, Francesco; Baba, Shinichi; Takihara, Hiroshi; Tanaka, Shinwa; Kawara, Fumiaki; Azuma, Takeshi (Endoscopy International Open, 2017)
Background and study aims A 54-year-old man was diagnosed with a rectal tumor extending through the submucosal layer. The patient refused surgery and therefore endoscopic submucosal dissection (ESD) was pursued. The lesion exhibited the muscle retraction sign. After dissecting circumferentially around the fibrotic area by double tunneling method, a myotomy was performed through the internal circular muscle layer, creating a plane of dissection between the internal circular muscle layer and the external longitudinal muscle layer, and a myectomy was completed.The pathologic specimen verified T1b grade 1 sprouting adenocarcinoma with 4350 µm invasion into the submucosa with negative resection margins.